Bessel Beam Diffraction by an Aperture in an Opaque Screen - Husnu Deniz Basdemir (International Journal of Optics)
The scattering of the Bessel beam by a circular aperture in an opaque screen is investigated by the geometrical theory of diffraction approach. The geometrical optics and diffracted and scattered fields are obtained. The effect of the aperture to the scattering process is analyzed. The uniform versions of field expressions are derived. The geometrical optics and diffracted and scattered fields are examined numerically.